School closures help reduce the spread of COVID-19: A pre- and post-intervention analysis in Pakistan. - Abdul Mueed; Razia Aliani; Mujahid Abdullah; Twangar Kazmi; Faisal Sultan; Adnan Khan (Public Library of Science (PLoS), 2022)
Closing schools to control COVID-19 transmission has been globally debated, with concerns about children's education and well-being, and also because of the varied effectiveness of the intervention in studies across the world. This paper aims to determine the effect of school closure policy on the incidence of COVID-19 in Pakistan. A Difference-in-Differences (DiD) analysis compared changes in COVID-19 incidence across cities that completely (Islamabad) and partially (Peshawar) closed schools during the second wave of COVID-19 in Pakistan. Effects of closing (November 2020) and reopening schools (February 2021) were assessed in Islamabad and Peshawar 10 and 20 days after policy implementation. In Islamabad, there was a greater decline in cases than in Peshawar when schools closed. After 10-days, the average reduction of daily COVID-19 incidence in Islamabad was lower by 89 cases (95% CI: -196, 18), due to complete school closure, with a relative reduction of 125 cases (95% CI: -191, -59) compared to Peshawar. Similarly, the relative increase in Islamabad after schools re-opened was 107 cases (95% CI: 46, 167) compared to Peshawar. After 20-days, the average daily COVID-19 incidence in both cities declined after school were closed (Islamabad: -81 [95% CI: -150, -13] versus Peshawar: -80 [95% CI: -148, -12]). COVID-19 incidence appeared to decline after schools reopened as well (Islamabad: -116 [95% CI: -230, -3] versus Peshawar: -30 [95% CI: -124, 63]). However, Peshawar's decline is not statistically significant. These results control for changes in testing as well as a daily time trend. The magnitude and speed of reduction in cases with a complete school closure, and a similar but reverse trend of increasing cases upon reopening, suggests that closing schools reduces COVID-19 transmission in communities. However, there are learning-loss and well-being costs for children and their parents.